Critical Analysis on the Contribution Made by Qualitative Research to English Language Teaching - Elmiana, Dewi Satria (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2017)
The primary objective of this paper is to assert the contribution of qualitative research in ELT. This paper has presented qualitative theories and features advantages and limitations, the criteria of good qualitative research, and analysis of two articles based on Tracy‟s model. The analysis result showed that both articles have some limitations such as the uncovering of potential resources and perspectives on how effective extensive reading programs should be implemented in tertiary education in Indonesia. However, most of the criteria that Tracy established were found in these articles, such as relevance of the area of study, timeliness and significance; sufficient, abundant, appropriate and complex use of theoretical constructs, as well as data collection and analysis processes.